A di-boron pair doped MoS2 (B2@MoS2) single-layer shows superior catalytic performance for electrochemical nitrogen activation and reduction. Issue 40 (8th October 2019) - Li, Fuhua; Tang, Qing
Abstract : Non-metal di-boron doping into a S-defective MoS2 single-layer is hypothesized as a promising electrocatalyst for N2 reduction at a close-to-zero overpotential. Abstract : Developing efficient electrocatalysts to convert nitrogen into ammonia represents a major chemistry challenge and is of great significance for sustaining life. A lot of recent studies have been focusing on the single-atom electrocatalysts for the N2 reduction reaction (NRR), yet the double-atom or few-atom catalysts, based on the non-metal catalytic center, in particular, have been rarely investigated. Herein from DFT simulations, we report diatomic boron doped single-layer MoS2, B2@MoS2, as the potential electrocatalyst for the nitrogen reduction reaction, and compare it with single boron atom doped MoS2, B@MoS2, based on thermodynamics, selectivity, and kinetics analysis. The results reveal that this novel diatomic modified catalyst exhibits excellent structural and thermodynamic stability, and shows significant improvement in the conductivity of MoS2 which is essential for the electrocatalytic NRR. Furthermore, the B2@MoS2 catalyst can effectively activate the inert N2 and promote N2 reduction to NH3 via the enzymatic mechanism, and shows much better electrocatalytic activity than B@MoS2, as reflected by the significantly reduced overpotential (0.02 V vs. 0.30 V) and the much lower activation barrier (1.24 eV vs. 2.84 eV). Particularly, the close-to-zero overpotential predicted for B2@MoS2 is lower than those of most ever-reported single-atom electrocatalysts. The extraordinary activity of B2@MoS2 is closely related to the efficient electron transport as well as the synergism effect of diatomic boron. Our predictions hence suggest B2@MoS2 as a superior promising catalyst for efficient dinitrogen fixation and reduction.